Ch’ixi, Qhipnayra, Nkali: modi di dire l’emergenza decoloniale (Altre Modernità, 2016)
This work stems from the notions of pensamento abissal, monocultura and ecologia de saberes (Sousa Santos: 2009) and applies them to the problem of the persistence of a form of coloniality surviving the age of political decolonization in the sphere of knowledge validation. The study analyses some reflections of the Bolivian Aymara sociologist Silvia Rivera Cusicanqui on the vocabulary of the Aymara language, spoken in Bolivia, who takes into account the native language universe and its expressive possibilities to pave the way for an epistemological decolonization. By analysing the proposal of the Bolivian sociologist and by relating it to other concepts, such as the one suggested by Nigerian writer Chimamanda Ngozi Adichie – who considers the Igbo language to formulate the idea of danger of a single story –, this study aims at presenting some ‘words that say’ that decolonization is not over and that decoloniality is still an emergency.
Keywords: epistemologie del Sud; decolonialità; ch’ixi; ecologia dei saperi; pensiero post-abissale